Climate of Inquiry and Critical Reflection Element in Teaching and Learning in Higher Education Institutions (Sains Humanika, 2018)
The purpose of this study is to explore the importance of climate of inquiry and critical reflection in teaching and learning. The study was established by using Teaching and Learning Guiding Principles Instrument (TLGPI) to identify the reliability and validity of the instrument in generating teaching and learning guiding principles (TLGP). Participants consisted of 355 Malaysian educators from higher education institutions and teacher training institutions. It is an essential instrument to reflect in generating the teaching and learning guiding principles in higher education level in Malaysia. Confirmatory Factor Analysis has validated all five items of Climate of Inquiry (CI) construct of TLGPI whereby all items indicated high reliability and internal consistency. A Confirmatory Factor Analysis also confirmed that a single factor model was used to generate teaching and learning guiding principles.
Keywords: Teaching and learning guiding principles; climate of inquiry; critical reflection; higher education institutions; confirmatory factor analysis